ANALISIS KETEPATAN PENENTUAN KODE SEBAB DASAR KEMATIAN (UNDERLYING CAUSE OF DEATH) DI RSUD HAJI PROVINSI JAWA TIMUR - Sabran Sabran; Lu'aily Munawaroh; Ervina Rachmawati (Jurnal Medika Malahayati, 2023)
One of the professional standards that must be mastered by medical recorders is coding the underlying cause of death (UCOD) and using the Medical Mortality Data Sheet (MMDS). MMDS along with ICD 10 assisted by the Guidebook for Determining the Cause of Death Code According to ICD-10 is used to determine the diagnosis code for the underlying cause of death. The purpose of this study was to analyze the accuracy of determining the basic cause of death code at the East Java Province Hajj Hospital. This study used a descriptive type of retrospective approach with the subject of 2 coding officers and the object of death reports in February and 56 cause of death certificates. The percentage of accuracy of UCOD determination at the East Java Province Hajj Hospital in February 2023, amounted to 21.4% accurate, and 44.6% inaccurate, and 33.9% unfilled. From the percentage results, it is known that the accuracy of code determination is still low, this is because there is no standard coding operational procedure and the guidelines for MMDS table tools have not been used. To assist in determining the basic cause of death code, coding training and socialization on how to determine the basic cause of death code and the provision of the Medical Mortality Data System (MMDS) table are needed.Keywords : Underlying Cause of Death, certificate, MMDS